A more complete, complexed and structured interactome - Devos, Damien; Russell, Robert B. (Current opinion in structural biology, 2007)
Multiprotein complexes are key players in virtually all important cellular processes. The past year has seen the publication of several papers that have illuminated what we know about the number and composition of these molecular machines, using high-throughput purification methods. Other studies have illuminated structural and functional aspects of protein interactions, networks and molecular assemblies. As a result, we have a more complete view of how many complexes are in living systems, what they look like and the roles they play in the cell.